A percepção do professor sobre as relações interpessoais no ensino da matemática - Machado, Karina de Oliveira (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T18:51:53Z (GMT). No. of bitstreams: 1 000396009-Texto+Completo-0.pdf: 490540 bytes, checksum: b56c1366199b9e1654ac1cf692088b1c (MD5) Previous issue date: 2007 === This study investigates the opinions of six mathematics teachers from three public elementary schools in Porto Alegre on interpersonal relationship and its influence on the teaching-learning process. Also investigated the relationships between teacher and students as a stimulant for learning. To do that, I worked with the mathematics teacher’s communication modalities and their stance on the importance of human relations in a classroom. I observed their speech, the way they developed communications and social networking with the students, in semi-structured interviews. During this research, I reinforced the belief in the power of the affectional bond established with the students in the learning process for the formation of capable and aware individuals. The main goal of the research was to analyze the opinions of the elementary school mathematics teachers in state public schools on the influence of interpersonal relationships in the teaching-learning process of mathematical content. In order to deepen the subject I prompted questions that evoked the daily classroom routines at the parents-teachers meeting.This research has relevancy, for it makes one think about interpersonal relationships as propellers of the desire to learn and to spark the students’ interest and curiosity. It also evokes the context of the ever so necessary guidelines/boundaries in a classroom. The teacher must know what to do, how to do it and, therefore, how to relate to and make demands from others, because only then the conditions for the occurrence of the learning and of the teaching will have been created. === Este estudo investiga as opiniões de seis professores de Matemática, de três escolas de Ensino Fundamental, na Rede Pública de Porto Alegre, sobre o relacionamento interpessoal e sua influência no processo de ensino e aprendizagem. Também pesquisei as relações do professor com os alunos como estimulador da aprendizagem. Para isso, trabalhei com as modalidades de comunicação do professor de Matemática e seus posicionamentos sobre a importância das relações humanas em sala de aula. Observei suas falas, o modo como teciam as comunicações e redes de relações com os alunos, em entrevistas semi-estruturadas. Durante esta pesquisa, reforcei a crença na força do vínculo afetivo estabelecido com os alunos no processo de aprender, para a formação de pessoas conscientes e capazes.O objetivo principal da pesquisa foi analisar as opiniões dos professores de Matemática, do Ensino Fundamental, de escolas públicas estaduais, sobre a influência dos relacionamentos interpessoais no processo de ensino e aprendizagem dos conteúdos matemáticos. Para aprofundar o tema direcionei questões que remetessem ao cotidiano das situações de sala de aula, no encontro entre professor e alunos. Esta pesquisa tem relevância, à medida que faz pensar sobre os relacionamentos interpessoais como propulsores do desejo de aprender e de despertar o interesse e a curiosidade dos alunos. Também remete ao contexto dos parâmetros/limites tão necessários em sala de aula. O professor precisa saber o que faz, como faz e portanto, como deve-se relacionar e exigir do outro, pois só assim serão criadas as condições para que ocorram o ensino e a aprendizagem.